2022
DOI: 10.1155/2022/6488935
|View full text |Cite|
|
Sign up to set email alerts
|

Predictive Value of Serum Markers SFRP1 and CC16 in Acute Exacerbation of Chronic Obstructive Pulmonary Disease

Abstract: Background. Chronic obstructive pulmonary disease (COPD) patients are particularly vulnerable to acute exacerbation, resulting in a huge socioeconomic burden. Objective. In this study, we evaluated the value of serum secreted frizzled-related protein 1 (SFRP1) and Clara cell-secreted protein (CC16) in predicting the risk of acute exacerbations in patients with COPD. Methods. The study included 123 COPD patients admitted to our hospital from May 2020 to June 2021, including 65 patients in stable stage (STCOPD g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…14 Another biomarker focused in our study is Clara cell secretory protein-16 (CC16), a major functional protein secreted by Clara cells. 15 In COPD, inflammation, oxidative stress and increased alveolar-capillary permeability significantly enhance the expression of CC16. CC16 can inhibit phospholipase A2 activity and reduce cell membrane phospholipid catabolism, and also directly inhibit the expression of various inflammatory factors and their biological activities, which play an important role in the development mechanism of asthma, COPD, and acute lung injury.…”
Section: Introductionmentioning
confidence: 99%
“…14 Another biomarker focused in our study is Clara cell secretory protein-16 (CC16), a major functional protein secreted by Clara cells. 15 In COPD, inflammation, oxidative stress and increased alveolar-capillary permeability significantly enhance the expression of CC16. CC16 can inhibit phospholipase A2 activity and reduce cell membrane phospholipid catabolism, and also directly inhibit the expression of various inflammatory factors and their biological activities, which play an important role in the development mechanism of asthma, COPD, and acute lung injury.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that SFRP1, as a member of the largest family of Wnt signaling pathway inhibitors, is involved in the occurrence and development of COPD by competitively binding to Frizzled receptor on the cell membrane to inhibit the Wnt pathway. 10,61 By analyzing the transcriptome of wild-type and mutant lungs, Wnt/RYK signaling was observed to regulate chronic obstructive pulmonary disease by up-regulating inflammatory genes in vitro. 62 These data suggest that Wnt signaling is important to avoid an overwhelming and harmful inflammatory response during acute infection.…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%